Program Ipteks Bagi Masyarakat Pengelolaan Usaha Warung Makanan Tradisional Daerah Primitif Bumi Perkemahan Air Terjun Dlundung Kemil Trawas Mojokerto - Efina Krinala; Fauzi Hidayat; Slamet Nur Fauzi; Anggun Puspita Sari; Wahyudi Wahyudi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
This community devotion aims to foster and contribute to the traders food stalls and traditional drinks that exist in the area of primitive mountains Waterfalls Camp Dlundung kemil Trawas. The results of our field observations and interviews with all three partners according to their food stall business partners are difficult to develop and there is even a tendency of profit gained less. This is because of the difficulty of raising the food price despite the increase in the price of the materials at any time, such as the price of rice that is rising significantly, the price of chili and vegetables is very volatile, while there is a tendency price of chicken and chicken eggs Soar. The tight business competition is also a consideration of raising food prices. In the position of competition, the increase in the income of business partners that are coupled with the effort can continue to grow and survive in the middle of existing competition, can be achieved through increasing sales turnover or scaling the business scale. The way to do this is to provide the best and satisfying service to the consumer, as well as maintain the quality of taste and improve the quality of the products so that the traditional stalls in the primitive regions can improve the level of life and can improve the economy. The research method is done by mentoring and training in understanding the cleanliness and quality of food stalls, business management assistance from the formulation of business plans, counseling and guidance of financial processing, comparative study To other food centers in Surabaya. The results of the research are expected to help the food for the overall mentoring to the traditional Warung traders and is expected to change the mindset of traders and pay more attention to the level of quality of products sold so that it can Increase the status of life significantly and can gain the maximum profit from visitors or customers of the land of Trawas waterfall camp. Key Word : Business Warung Food and beverage Traditional